X SHIP COOLING SYSTEM FAILURE ANALYSIS (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2021)
Indonesia as an archipelagic country has 17,100 islands which are bordered by waters. Because of the vast territorial waters of Indonesia, this country needs many ships as a means of transportation and means to support Indonesia's abundant marine products and massive inter-island transportation. For that PT. DKB builds an X Double Engine type ship equipped with a RAS (Replenishment at Sea) system, which is a ship to help transfer fuel at sea. However, the engine has not functioned optimally due to excessive engine heat, which is the heat released by the engine so that the efficiency of the ship's engine decreases. The heat of the engine is probably caused by a problem with the cooler that is not able to serve the needs of the main engine. For this reason, it is necessary to re-examine this matter so that the engine performance is optimal.